Kinematic differences between gradual and impulsive coronal mass ejections: the role of flares - Hamidi, Z.S.; Mohamad Ansor, N.; Shariff, N.N.M. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Coronal Mass Ejections (CMEs) are significant solar events that involve intense explosions of magnetic fields and mass particles out from the corona. These events are known to be the main driver of space weather and other disturbances experienced by the Earth. Generally, there are two types of CMEs – gradual and impulsive, and each type has different properties which is important to be studied on as they have potential to cause breakdowns in our systems. This study is aimed to analyze and differentiate the kinematic behavior of gradual and impulsive CME with the association of weak and strong flares. Data collection is made through SOHO LASCO catalogues and STEREO database which include velocity, acceleration and angular width as well as images. At the end of this study, it can be deduced that impulsive CME (specifically associated with strong flare) is the most prominent event that has greatest angular width and average velocity. The associated flare has contributed more heat energy to speed up the magnetic energy conversion which results to high velocity of plasma discharge. Since fast CME carries huge amount of momentum during the ejection, impulsive CMEs also experience decelerations due to loss of momentum that has been transferred to background solar wind.